A non-invasive method to estimate glucose levels in salivary secretions of diabetic patients - Peddi, Pramod Kumar Reddy; Singanamala, Chandra Babu; Mounija, Cheemalavagupalli (International Journal of Research in Medical Sciences, 2019)
Background: Aim of the study is to correlate between blood glucose levels and salivary glucose levels in type 2 diabetic patients, to study the relationship between salivary glucose levels and serum glucose levels in type 2 diabetic patients and to determine whether salivary glucose levels could be used as a non-invasive tool for the measurement of glycemic control in type 2 diabetics. This requirement of multiple pricking at regular intervals for monitoring serum glucose levels in the body is physically and psychologically traumatic to the patient. This necessitates a non-invasive procedure like salivary glucose estimation. Methods: The study population consisted of two groups: Group 1 consisted of 20 controlled diabetics and Group 2 consisted of 20 diabetics based on their random blood and salivary glucose levels. Two milliliters of peripheral blood were collected for the estimation of random blood glucose levels. Unstimulated saliva was collected by the oral rinse technique for the estimation of salivary glucose. Results: ANOVA single factor and Pearson correlation coefficient was carried out to know the statistical significance between the two groups. The salivary glucose levels were significantly higher in controlled and when compared with the diabetics. The salivary glucose levels showed a significant correlation with blood glucose levels, suggesting that salivary glucose levels can be used as a monitoring tool for predicting glycemic in diabetic patients. Conclusions: The present study found that estimation of salivary glucose levels can be used as a non-invasive, painless technique for the measurement of diabetic status of a patient in a dental set up.